Pengembangan Media Bimo Bilawa untuk Pembelajaran Unggah-Ungguh Basa Jawa Siswa Sekolah Dasar - Nurkharima, Albashita; Putriani, Ida; Fauzi, Adin (Faculty of Teacher Training and Education, Musamus University, 2022)
Bimo Bilawa media is a media development of Javanese language uploading and learning media to improve the ability of teachers and the spirit of learning for students in elementary schools. This research was conducted to process Bimo Bilawa media for Javanese language material at the elementary school level. This research is a research and development research that includes: (1) potentials and problems, (2) data collection, (3) product design, (4) design validation, (5) design revision, (6) product testing, (7) product revision. The subjects of the literacy test were 40 students in grades 4 and 5, as well as 4 teachers in grades 4 and 5 at SDN Sidodadi 4 and SDN Karangrejo 1. The data collection technique uses questionnaires and interviews. Data analysis techniques use quantitative and qualitative descriptive. The results of the assessment of material experts received a percentage of 96% with a very feasible category. The results of the assessment of linguists and media experts obtained a percentage of 93% categorized as very feasible. In the readability test, the teacher obtained a percentage of 94.5%, which was categorized as very feasible. So that Bimo Bilawa media can help teachers in the learning process. In the readability test, students obtained a percentage of 99%, categorized as very feasible. The students seemed to enjoy the media equipped with sounds and graphic images, and they were excited to try learning with Bimo Bilawa media.